REINTERPRETASI HUKUM POTONG TANGAN DALAM QS AL MAIDAH AYAT 38 PERSPEKTIF PENDEKATAN SISTEM JASSER AUDA - Alfi Nur'aini (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
The interpretation of the law of hand amputation in Surah Al-Maidah verse 38 often conveys an impression of Islamic law as rigid, static, inhumane, and contrary to human rights. This study seeks to reinterpret this law through the system approach to Islamic jurisprudence developed by Jasser Auda, a contemporary expert in Islamic law. Auda, renowned for his expertise in systems analysis and maqasid syariah, endeavors to reform Islamic legal principles to better align with contemporary issues. He employs maqasid syariah as the foundation for his systematic approach, serving as his methodology and analytical tool. Auda’s framework comprises six key features: cognitive nature, wholeness, openness, interrelated hierarchy, multidimensionality, and purposefulness. By applying these features, the study aims to reinterpret the law of hand amputation into a more flexible, dynamic, and contextually appropriate form. Rather than a rigid application, the law should consider the varying contexts in which it is implemented, ensuring it aligns with current societal values and human rights standards